Profitability and productivity barriers and opportunities in small-scale irrigation schemes - Bjornlund, Henning; Rooyen, Andre F. van; Stirzaker, Richard (Informa UK Limited, 2017)
Irrigation development in Sub-Saharan Africa has lagged significantly behind that in other developing countries. Consequently, economic development and food security are also lagging behind. Since the mid-2000s there has been a resurgence in the willingness to invest in irrigation, and Sub-Saharan Africa has the largest potential of any developing region to benefit from it. However, to gain from new investment in irrigation without repeating past failures, it is critical to develop a business model for small-scale irrigation schemes. This article explores the barriers that such a model needs to address to be successful and the opportunities this represents for irrigators’ profitability.